PENYAJIAN LAPORAN KEUANGAN, SISTEM PENGENDALIAN INTERNAL DAN AKSESIBILITAS LAPORAN KEUANGAN PADA AKUNTABILITAS PENGELOLAAN KEUANGAN DAERAH - Menrokis Purba; Restu Agusti; Rofika Rofika (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2021)
This study aims to examine the effect of the presentation of financial statements, internal control systems and accessibility of financial reports on the accountability of regional financial management. The population in this study were 23 opd within the Pematangsiantar city government. The sampling technique used in this research is purposive sampling. The data were processed using SPSS version 25 and analyzed using multiple linear regression analysis. The dependent variable in this study is the accountability of regional financial management. The independent variables used in this study are the presentation of financial statements, the internal control system and the accessibility of financial statements. The results of this study indicate that the presentation of financial statements affects the accountability of regional financial management, the internal control system affects the accountability of regional financial management, the accessibility of financial reports affects the accountability of regional financial management.